Analisis Pengaruh Brand, Harga Dan Iklan Terhadap Loyalitas Konsumen Air Mineral Merek Aqua (Survey Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Dewi, Yosi Puspa; , Basworo Dibyo, S.E, M.Si (2016)
This study was motivated by the increasing number of diverse businesses that develop, one that is Mineral Water Company. The increasing number of consumers who are aware of the cleanliness of the Mineral Water to be consumed, the higher the company that wants to engage in business in bottled mineral water. Intense competition makes companies must be proactive in response to changes in a dynamic environment. This study aimed to examine the effect of the variable of brand, price, and Ads on Consumer Loyalty Brand Mineral Water Aqua At the Faculty of Economics and Business, University of Muhammadiyah Surakarta. After review of the literature and formulation of hypotheses, data were collected through questionnaires to 100 respondents Faculty of Economics and Business, University of Muhammadiyah Surakarta who consume Mineral Water Aqua obtained using random sampling techniques. Then conducted an analysis of the data obtained by quantitative data. Quantitative analysis includes: validity, reliability, multiple linear analysis, hypothesis testing via t test and F, as well as the analysis of the coefficient of determination (R2). The data that has met the test of validity, reliability test processed by SPSS (Statistical Package for Social Science).